2019
DOI: 10.15446/abc.v24n3.79277
|View full text |Cite
|
Sign up to set email alerts
|

Coinfección natural de virus de ARN en cultivos de papa (<i>Solanum tuberosum</i> subsp. Andigena) en Antioquia (Colombia)

Abstract: Citation/Citar este artículo como: Gallo Y, Sierra A, Donaire L, Aranda M, Gutiérrez PA, Marín M. Coinfección natural de virus de ARN en cultivos de papa (Solanum tuberosum subsp. Andigena) en Antioquia (Colombia). Acta biol. Colomb. 2019;24(3):546-560. DOI: http://dx.doi.org/10.15446/abc. v24n3.79277 RESUMENLas enfermedades virales son uno de los principales problemas fitopatológicos de la papa. Con el fin de determinar los virus más prevalentes en cultivos de papa var. Diacol Capiro en el oriente Antioqueño … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
2
0
4
Order By: Relevance
“…Within Antioquia, potato production is concentrated in the eastern and northern regions, the latter of which comprises fields totaling 3585 ha across the municipalities of Santa Rosa de Osos, Entrerríos, San Pedro de los Milagros, and Belmira. Recent investigations on the viruses transmitted through seed-tubers in potato fields in eastern Antioquia have revealed a high prevalence of RNA viruses in formal-and informally-produced planting material, and it is believed that high viral loads are a major factor explaining the lower potato productivity of the region (Sierra et al, 2020;Gallo et al, 2019;2021b). For example, in a study on seed-tubers from the Diacol Capiro cultivar it was found a prevalence for potato yellow vein virus (PYVV) of 73.3%, and up to 90% for potato virus Y (PVY) (Sierra et al, 2021).…”
Section: _______________________________________________mentioning
confidence: 99%
“…Within Antioquia, potato production is concentrated in the eastern and northern regions, the latter of which comprises fields totaling 3585 ha across the municipalities of Santa Rosa de Osos, Entrerríos, San Pedro de los Milagros, and Belmira. Recent investigations on the viruses transmitted through seed-tubers in potato fields in eastern Antioquia have revealed a high prevalence of RNA viruses in formal-and informally-produced planting material, and it is believed that high viral loads are a major factor explaining the lower potato productivity of the region (Sierra et al, 2020;Gallo et al, 2019;2021b). For example, in a study on seed-tubers from the Diacol Capiro cultivar it was found a prevalence for potato yellow vein virus (PYVV) of 73.3%, and up to 90% for potato virus Y (PVY) (Sierra et al, 2021).…”
Section: _______________________________________________mentioning
confidence: 99%
“…1). El hallazgo del PVB en cultivos de papa en Colombia es el primer registro de este virus por fuera del Perú (De Souza et al, 2017); los virus restantes ya han sido reportados en múltiples ocasiones para ambos hospedantes en esta región del oriente de Antioquia (Gutiérrez et al, 2016;Vallejo et al, 2016;Gallo et al, 2019;Sierra et al, 2020) y por tanto los resultados que se describen a continuación se centrarán en la caracterización del genoma de este nepovirus, cuya secuencia fue depositada en GenBank con los números de accesión MT521733 y MT521734 con el nombre del aislamiento PVB_phureja.…”
Section: Secuenciación De Alto Rendimiento (Hts)unclassified
“…Lagerh) y diversas enfermedades de origen viral (Navas y Díaz, 2012). Los agentes causales de las enfermedades virales hasta ahora detectados en este cultivo en Antioquia incluyen Potato leafroll virus (PLRV), Potato mop-top virus (PMTV), Potato virus S (PVS), Potato virus V (PVV), Potato virus X (PVX), Potato virus Y (PVY) y Potato yellow vein virus (PYVV) (Sánchez et al, 1991;Gil et al, 2011Gil et al, , 2012Gil et al, , 2013Guzmán et al, 2012;Villamil-Garzón et al, 2014;Álvarez et al, 2016;Gutiérrez et al, 2016;Mesa et al, 2016;Vallejo et al, 2016;Gallo et al, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…En este caso, en muestras de semilla no certificada del cultivar Diacol Capiro, el promedio de coinfección fue de 4,6 virus por muestra, con un número mínimo de 4 y máximo de 6 virus, mientras que, en material certificado, el promedio de coinfección fue de 4 virus por muestra, con valores mínimos y máximos de 2 y 6 virus, respectivamente. Estos resultados, en su conjunto, aunque resultan muy alarmantes para la agroindustria de papa en Colombia, no son inesperados, por cuanto trabajos previos de detección de virus realizados directamente sobre material foliar de plantas de papa en estado de floración en Antioquia, han registrado niveles de infección del 88,9 %, para PVY, 75 %, para PVX y PYVV, 41,7 %, para PLRV y 25 %, para PVS (Gallo García et al 2019).…”
Section: Secuenciación De Alto Rendimiento (Hts)unclassified